Conductas autodestructivas y anomia social en estudiantes de secundaria con y sin violencia intrafamiliar - Huerta Rosales, Rosa E. (2023)
The study analyzes the association between self-destructive indirect behaviors and social anomie in a sample of 509 fourth grade high school students from Lima. A data sheet, the Kelley et al. (1985) Self-destructive behaviors Scale adapted to Spanish language by Ponce (2007) and the Li et al. (1999) Anomie Scale validated by Vera et al. (2013) were applied. The study found direct and significant association between both variables in the total sample (in cases with and without domestic violence), with moderate effect. In cases without domestic violence, discontent is associated with all self-destructive behaviors’ dimensions, followed by distrust associated to four of them. In teenagers who are victims of domestic violence, discontent is associated with lack of planning and anticipation and neglecting their duties and distrust is associated with neglecting their duties. Finally, in accordance with the results from multivariate logistic regression analyses, the only dimension of social anomie statistically significant (p<.05) to predict self-destructive behaviors is discontent.